Transitioning student identity and sense of place: future possibilities for assessment and development of student employability skills. Issue 5 (4th May 2018) - Griffiths, David A.; Inman, Margaret; Rojas, Harriet; Williams, Kent
ABSTRACT: Identification of and feedback on employability skills is a significant challenge across the tertiary education landscape, up to and including doctorate programmes (e.g. weak labour market demand for professional doctorates). Growing skills gaps and accelerated growth in technological capability are contributing to uncertainty across global labour market landscapes. The originality of our research is gained via an exploration of employability skills through the lens of Student Development Theory and Bloom's adapted taxonomy to produce and rigorously test a new employability skills maturity framework, delivered using a 360° analysis tool in a Midwestern University in the United States. Our findings identify significant gaps in current thinking, specifically a lack of consensus as to what constitutes employability skills and how they are levelled, that demonstrate the need for educational institutions to improve resources, challenges and support related to the awareness of graduate identity and self-perception of employability, if graduates are to remain relevant in rapidly changing labour market landscapes.